Vivaldi: Visualization and validation of biomacromolecular NMR structures from the PDB. Issue 4 (15th January 2013) - Hendrickx, Pieter M. S.; Gutmanas, Aleksandras; Kleywegt, Gerard J.
Abstract We describe Vivaldi (VIsualization and VALidation DIsplay; http://pdbe.org/vivaldi), a web‐based service for the analysis, visualization, and validation of NMR structures in the Protein Data Bank (PDB). Vivaldi provides access to model coordinates and several types of experimental NMR data using interactive visualization tools, augmented with structural annotations and model‐validation information. The service presents information about the modeled NMR ensemble, validation of experimental chemical shifts, residual dipolar couplings, distance and dihedral angle constraints, as well as validation scores based on empirical knowledge and databases. Vivaldi was designed for both expert NMR spectroscopists and casual non‐expert users who wish to obtain a better grasp of the information content and quality of NMR structures in the public archive. © Proteins 2013. © 2012 Wiley Periodicals, Inc.